2019
DOI: 10.1007/s11886-019-1178-9
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Functional Cardiac Tissues for Regenerative Medicine Applications

Abstract: Purpose of Review Tissue engineering has expanded into a highly versatile manufacturing landscape that holds great promise for advancing cardiovascular regenerative medicine. In this review, we provide a summary of the current state-of-the-art bioengineering technologies used to create functional cardiac tissues for a variety of applications in vitro and in vivo. Recent Findings Studies over the past few years have made a strong case that tissue engineering is one of the major driving forces behind the acceler… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 152 publications
(178 reference statements)
0
28
0
Order By: Relevance
“…These trials demonstrated feasibility and safety of clinical translation of hESC-derived cardiovascular progenitors, paving the way for further efforts of efficacy studies. Recently, CPCs have shown promise as a highly reproductive cell source in additive cardiac tissue manufacturing, as an alternative to the non-proliferative, mature CMs, to create highly cellularized function hCMPs (92)(93)(94).…”
Section: Progenitor Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…These trials demonstrated feasibility and safety of clinical translation of hESC-derived cardiovascular progenitors, paving the way for further efforts of efficacy studies. Recently, CPCs have shown promise as a highly reproductive cell source in additive cardiac tissue manufacturing, as an alternative to the non-proliferative, mature CMs, to create highly cellularized function hCMPs (92)(93)(94).…”
Section: Progenitor Cellsmentioning
confidence: 99%
“…Conventional methods for manufacturing hCMPs include generating contiguous sheets of cardiac cells (mainly CMs) or suspending cells of a variety of types in scaffolds of biocompatible material (94,(105)(106)(107)(108). More recently, the emergence of 3D printing technologies, combined with cell-containing "bioinks" and computer-aided design (CAD), has enabled researchers to define the architecture of hCMPs with previously unattainable precision (Figure 3).…”
Section: Advanced Cardiac Tissue Manufacturing Strategiesmentioning
confidence: 99%
“…However, as mentioned previously, the canonical 2D culture and differentiation of these cells still has major limitations, most notably their immature phenotype, which lacks to fully represent developed tissue. The development of new biomaterials (Reis et al, 2016;Wissing et al, 2017;Kuraitis et al, 2019) and the emerging of new technologies such as tissue printing (Charbe et al, 2019;Tomov et al, 2019), organ on a chip (Marsano et al, 2016;Ugolini et al, 2018;Wan et al, 2018), and different types of bioreactors that allow mechanical, perfusion, or electrical stimulation (Freed et al, 2006;Lei and Ferdous, 2016;Paez-Mayorga et al, 2019) allow us to generate cardiac tissue that more closely recapitulate the (patho)physiological features of the developed myocardium. Moreover, these models represent an optimal tool not only to test and validate new drugs or to re-create tissue substitute for regenerative medicine application but also to allow a better understanding of the molecular mechanisms behind disease development and progression.…”
Section: Conclusion and Future Perspectivementioning
confidence: 99%
“…A biomimetic biomaterial can be any scaffolding material that mimics the characteristics of the natural ECM. They are based on polymers that may be natural, synthetic or biosynthetic (26,28). They are interesting for the repair and regeneration of tissues due to their biodegradability, mechanical properties or high porosity.…”
Section: A) Biomimetic Scaffoldsmentioning
confidence: 99%